Tenth year reenrollment randomized trial investigating the effects of childhood probiotics and calcium supplementation on height and weight at adolescence. - Setiawan, EA; Rianda, D; Kadim, M; Meilianawati; Susanto, F; Kok, FJ; Shankar, AH; Agustina, R (Springer Nature, 2021)
Microbiota and its modification with specific probiotics in early life could provide long term health benefits. Probiotics and calcium strengthen intestinal integrity and may support linear growth. This study investigated the long-term effects of childhood probiotics and calcium supplementation on growth in adolescence. We re-enrolled 238 adolescents aged 11-18 years from 494 children 10-years after 6-months of supplementation with either low-lactose milk fortified with low levels of calcium (LC, ∼50 mg/day, n = 53/124), with regular levels of calcium (RC, ∼440 mg/day, n = 70/126), or with regular calcium + 5 x 108 CFU/day Lactobacillus reuteri DSM 17938 (Reuteri, n = 55/124), or regular calcium + 5 x 108 CFU/day L. casei CRL 431 (Casei, n = 60/120). Changes in height-for-age z-score (HAZ) and body mass index-for-age z-score (BMIZ) were determined from the end of intervention to re-enrollment. General linear models were used to assess the effects on HAZ and BMIZ of group, gender, living area, maternal education, family income, physical activity, diet quality, nutritional status, and gut integrity as determined by urinary lactulose/mannitol ratio (L:M). Adolescent mean age was 15.3 years, mean HAZ was - 1.11, mean BMIZ was - 0.2 and median L:M (n = 155) was 0.23. Changes in HAZ and BMIZ were not significantly different between Casei, Reuteri, LC compared to RC. However, a significant decrease in BMIZ was observed among female adolescents in the Casei compared to RC group (- 0.5 SD, 95% CI - 0.8 to - 0.003, p = 0.048). Childhood probiotic and calcium supplementation may therefore selectively affect female adolescents.Clinical trial registration: This follow-up study has been registered at www.clinicaltrials.gov , Registry name: Rina Agustina, Registration number: NCT04046289, First Registration Date 06/08/19. web link: https://www.clinicaltrials.gov/ct2/show/NCT04046289 .